Improvement of Thermoelectricity Through Magnetic Interactions in Layered Cr2Ge2Te6. Issue 9 (4th June 2018) - Peng, Chengxiao; Zhang, Guangbiao; Wang, Chao; Yan, Yuli; Zheng, Haiwu; Wang, Yuanxu; Hu, Ming
Abstract : The magnetism is proposed as a way to improve thermoelectricity, which may overcome the tradeoff between electrical conductivity and Seebeck coefficient. The correlation between magnetic configurations and thermoelectricity in layered magnetic semiconductor Cr2 Ge2 Te6 has been investigated using first‐principles calculations, combined with semi‐classical Boltzmann theory. The electronic structures and relevant transport properties for paramagnetic phase have been stimulated. Special quasi‐random structure (SQS) is employed to simulate electronic properties of paramagnetic state corresponding to spin‐disordered configurations. The temperature dependence of calculated Seebeck coefficient, electrical conductivity, and the figure of merit ZT is in good agreement with experimental values for paramagnetic phase. For p‐type Cr2 Ge2 Te6, the maximum ZT can reach 0.54 at 830 K and the carrier concentration a value of 2.1 × 10 20  cm −3 . The calculated figure of merit can further increase by 42% compared to the maximum experimental result by optimized doping level. Cr2 Ge2 Te6 without spin polarization shows a metal electric band structure, which deviates from the semiconductor of truth. This means that magnetic interactions play an important role in electronic structure and result in an excellent thermoelectricity of paramagnetic Cr2 Ge2 Te6 . High band valley degeneracy, flat valence bands, and the localized partial density of states (PDOS) of magnetic atoms near Fermi surface induce a large Seebeck coefficient, meanwhile a good electrical conductivity is maintained in this magnetic semiconductor with high symmetry. Abstract : High band valley degeneracy, flat valence bands, and the localized partial density of states (PDOS) of magnetic atoms near the Fermi surface result from spin exchange interactions among magnetic ions and high symmetry. They can cause the collaborative optimization of Seebeck coefficient and electrical conductivity, therefore an excellent figure of merit ZT is obtained at 830 K for paramagnetic Cr2 Ge2 Te6 .